Pengaruh Customer Experience dan Brand Trust Terhadap Customer Loyality Tamu di Hotel Truntum Padang - Perdi Al-Aziz; Hijriyantomi Suyuthie (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This research is based on customer loyalty, which is an important factor in retaining guests or customers. Based on good customer experience and brand trust, of course, customer loyalty will increase in guest or customer satisfaction in a company or hotel. However, from this, there are findings in this research conducted on guests at Truntum Hotel Padang, namely that there are still some guests who are not loyal and provide unfavourable comments on their experience staying at Truntum Hotel Padang. Therefore, the goal of this study is to analyse the impact of customer experience and brand trust on guest customer loyalty at Truntum Hotel Padang. The sample size in this research is 365 people with the criteria that guests who have stayed more than twice and are more than 21 years old at Hotel Truntum Padang. Data analysis method used is logistic regression analyse with SPSS version 23.00. The research results indicate that customer experience and brand trust partially and significantly influence the customer loyalty of Truntum Padang Hotel guests.